If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(x-5)/13 = (x-11)/14 // - (x-11)/14
(x-5)/13-((x-11)/14) = 0
(x-5)/13+(-1*(x-11))/14 = 0
(14*(x-5))/(13*14)+(-1*13*(x-11))/(13*14) = 0
14*(x-5)-1*13*(x-11) = 0
x+73 = 0
(x+73)/(13*14) = 0
(x+73)/(13*14) = 0 // * 13*14
x+73 = 0
x+73 = 0 // - 73
x = -73
x = -73
| 4x+2-x=7+x-3 | | -5(-10+6x)=-310 | | 3x^2+48x-7=0 | | 4x+2-x=12x+10-3x | | 4x-8+15x=13-2x+21 | | 18-5x-7=12x+11+17 | | 5n+8=45 | | 14x^2/7^-6 | | (x+2)(y-3)=10 | | 3d=51 | | 4-3log(5x)=16 | | 5x-11=4g+4 | | -5(7-4x)=145 | | y=(-x-8)/8 | | 2x^2-4x=300 | | X-1+3x+5+x+8=12 | | X-1+3x+5+x+8= | | V-4v=20 | | 7x-3+2x=8x+5 | | (x-5)(x-5)+x^2=(x+5)(x+5) | | 3x^5=48*2 | | y=-1+-0.125x | | x=600000-x/5 | | -5x+7+1=-17 | | 8y+8=-x | | 6(-2+7x)=492 | | F(x)=x*-8x+9 | | 11+2x=7+4x | | 4x+3-7x=16 | | 6x(x+1)=(2x+8)(x+1) | | 2-3=z-15 | | -3(6x-5)+19(x-9)=-141-5 |